Rabbinic tales of destruction: gender, sex, and disability in the ruins of Jerusalem - Belser, Julia Watts (Oxford University Press, 2018)
Analyzing early Jewish accounts of the destruction of the Second Temple, Julia Watts Belser illuminates the brutal body costs of Roman conquest. Drawing on disability studies, feminist theory, and new materialist ecological thought, Belser reveals how rabbinic discourses of gender, sexuality, and the body are shaped in the shadow of empire